The Impact of Using Reading Storybooks and Writing Journal Activities on Print and Phonemic Awareness of Jordanian Kindergarten Children - Ebtesam Q. Rababah (Sultan Qaboos University, 2017)
This study investigated the impact of reading storybooks and writing journal activities on print and phonemic awareness of Jordanian kindergarten children. Subjects participated in book-reading sessions with a print focus, and writing journals. A total of 50 children were recruited for the study from one kindergarten in Irbid City, Jordan. Two intact sections of 25 children each served as experimental and control groups. Pre-test measures of children's print and phonemic awareness were administered. Subsequently, children in the experimental group participated in 24 small-group reading sessions that included a print focus, and 14 writing journals over a 14-week period. As an alternate condition, control-group children participated in conventional instruction methods only. Post-testing indicated that children who participated in print-focused reading and writing journal sessions outperformed their control group peers on four measures of print awareness (words in print, print concepts, alphabet knowledge and letter discrimination, and literacy terms), and on phonemic awareness (letter sound identification, rhyme, phoneme blending, phoneme segmentation, and phonemic manipulation), as well as overall performance. Implications and future research directions are discussed.